2020
DOI: 10.1097/md.0000000000022740
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization and outcome of prolonged heart rate-corrected QT interval among children with syndactyly

Abstract: Prolonged heart rate-corrected QT (QTc) interval is an independent risk factor for sudden cardiac death, which is the hallmark of Timothy syndrome (TS). There are little data on children with syndactyly and QTc prolongation. To evaluate the characteristics and long-term outcomes in children with syndactyly, and to attempt to identify TS in patients with syndactyly and QTc prolongation. This is a retrospective case-control study of children with syndactyly who visited Beijing Jishuitan Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Moreover, the TWA trait was found to be associated with the QTc prolongation within syndactyly patients in Chinese children (Ref. 24 ).…”
Section: Molecular Mechanisms Underlying the Cacna1c ...mentioning
confidence: 99%
“…Moreover, the TWA trait was found to be associated with the QTc prolongation within syndactyly patients in Chinese children (Ref. 24 ).…”
Section: Molecular Mechanisms Underlying the Cacna1c ...mentioning
confidence: 99%
“…Recently, autosomal dominant SD has been associated with a microdeletion of 2.79 Mb at chr14q22-q22.2 in four affected members of a three-generation family with limb defects (syndactyly and polydactyly) along with other disorders, such as developmental delay and facial defects [67]. Recently, it has been reported that children with SD and prolonged heartrate-corrected QT (QTc) interval have more multisystem diseases and electrocardiographic abnormalities [68]. Heterozygous missense alterations in GLI3 (c.1622C>T;p.T541M) and GJA1 (c.274T>C;p.Y92H) were identified in patients with the phenotypic features of SD type I [69], and two variants (p.D1403H, p.Q1564K) of LRP4 have been reported in a child affected with isolated SD of both hands, although the LRP4 gene has been reported to cause SD7 [70].…”
Section: Some Excluded Types Of Syndactyly and Underlying Genetic Fac...mentioning
confidence: 99%